Aspergillosis in Lung Cancer: A Narrative Literature Review - Yarsy, Pofi Risanti; Sri Melati Munir (HM Publisher, 2024)
Aspergillosis is one of the complications of lung cancer and lung cancer treatment. Diagnosis of Aspergillosis in lung cancer, in general, is still a challenge because clinical symptoms and examination results are not typical, and risk factors often go unnoticed. To simplify the diagnosis of Aspergillosis, several criteria have been created based on the patient's condition, clinical and radiological features, and mycological laboratory examination. Doctors' vigilance still needs to be increased, examination facilities are still limited in certain cities, and diagnostic services have not been integrated, so management is not optimal. This literature review aims to increase doctors' knowledge and awareness regarding aspergillosis in lung cancer, which is an important step to improve the appropriate management of this disease.